Diseño De Un Sistema De Empaque Y Embalaje Para Alimentos Preparados Destinados A Personas Inscritas En Los Comedores Comunitarios Con Dificultades De Acceso En La Localidad De Ciudad Bolívar (2023)
You have to reduce everything that can be minimized and hide everything that can be hidden without losing the internal value, since you want the products to be easy to use, and also fulfill all the functions that the user requires for said purpose. product (Maeda, J. 2008).